Communication challenges in end-of-life decisions (Swiss Medical Weekly, 2020)
With the progress in healthcare over recent decades and a growing life expectancy, discussions and decisions regarding end-of-life issues have become increasingly important. Especially in intensive care and emergency medicine there is a growing need of decision making for optimised end-of-life care. Prolonging life and preventing death is considered to be the highest principle of healthcare professionals; however, in some cases alleviation of suffering is a more appropriate goal. This article discusses communication challenges in end-of-life decision making and outlines strategies from an area of growing interest and research.